Dúvida e culpa: um estudo sobre a problemática identificatória em um caso de neurose obsessiva - Scatolin, Henrique Guilherme (2014)
This study investigated the identificatory problematic in a case of obsessional neurosis. Thus, this analysis was based on four central pillars: the Oedipal resolution of patient Paul's parents, his libidinal and identificatory history, the incorporation of the sadistic penis and identification with the superego. The methodology of this study is based on the Freudian psychoanalytic theory of obsessional neurosis, the contributions of Piera Aulagnier to the Freudian metapsychology and psychopathology, as well as the reading of post-Freudian psychoanalysts about this neurosis and its contemporary manifestations, such as Lacan, Green, Bleichmar, Calligaris and Leclaire. Throughout the results, I have produced my floating theorisation, emphasizing the patient s reports and associations. Upon hearing his story, it was possible to understand the presence of his parents desire since his birth, underlining how the paternal function, next to the maternal, was always present in his constitution. Throughout this analysis, I have highlighted how aggression and hatred pointed toward his father, which also hold passive impulses towards him, have intensified throughout his psychic constitution, being repressed after the assumption of castration. These ambivalent movements became explicit in his symptomatic formations, manifesting his identificatory problematic. If, on the one side, along the psychotherapy, the positivity was gaining ground, giving a new destiny to his feelings and identificatory references, on the other side, such way has been achieved due to psychotherapeutic interventions focused on manifestations of the unconscious hatred and destructive feelings located in the intrincacies of his guilts, doubts and rituals (and that fed his resistances and paralyzations in the clinical setting), denoting that in his identificatory problematic, his debt towards his father was of the order of his own desire. This study concludes that the four central pillars are very important for elucidating the identificatory problematic in cases of obsessional neurosis, becoming interchangeable to guide the future analyst s look when he comes across the typical clinical manifestations of this neurosis